1966
DOI: 10.1530/acta.0.0530687
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Placental Transfer of Human Growth Hormone

Abstract: Fourteen healthy women were given intravenous injections of either high doses of non-labelled or tracer doses of 131I-labelled human growth hormone (HGH) between 270 and 10 minutes before delivery. The concentration of HGH in the plasma was followed at intervals up to delivery and then in the cord plasma and newborn infant. Both methods of study showed that growth hormone is not transferred from the mother to the foetus. An additional finding was the shortened biological half life (t½) of 131I-HGH in the women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0
1

Year Published

1970
1970
1997
1997

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 0 publications
1
18
0
1
Order By: Relevance
“…We have previously obtained genetic linkage data (2) strongly supporting the hypothesis that the hGHR gene identified by Leung et al (1) is involved in a genetic form of GH resistance (Laron syndrome) (3,4). This hypothesis was further reinforced by the description of interstitial GHR gene deletions in some such patients (18).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…We have previously obtained genetic linkage data (2) strongly supporting the hypothesis that the hGHR gene identified by Leung et al (1) is involved in a genetic form of GH resistance (Laron syndrome) (3,4). This hypothesis was further reinforced by the description of interstitial GHR gene deletions in some such patients (18).…”
Section: Discussionsupporting
confidence: 54%
“…One approach to this problem is to study diseases, from which clues on normal physiology can be gleaned. As a first step toward this goal, we showed that mutations in the GHR gene can be associated with Laron syndrome (2), an autosomal recessive GH-resistance disorder (3,4). This finding was particularly interesting since the amino-terminal amino acid sequences of GHR and serum GH-binding protein (GH-BP) (5) in various species are identical, suggesting that GH-BP is derived from the extracellular binding region of the receptor (6, 7), whereas serum from patients with Laron syndrome lacks functional GH-BP (8).…”
mentioning
confidence: 99%
“…Laron syndrome, a recessively inherited disease with growth hormone (GH) resistance, was first described in 1966 (1). To date, more than 220 cases have been reported worldwide.…”
mentioning
confidence: 99%
“…Laron-type dwarfism (LTD) is a rare, autosomal recessive disorder that is characterized by high circulating levels of biologically active GH accompanied by low levels of IGF-I (13)(14)(15)(16) and a failure to respond to GH therapy (15). Some individuals with LTD have been shown to lack GH binding in liver biopsy samples (17), to lack GH binding activity in their serum (18)(19)(20), or to lack an IGF-I response in transformed T lymphoblasts (21).…”
mentioning
confidence: 99%